The Ethical, Political and Economic Challenges of Effective Altruism - Kucz, Mateusz; Rosół, Piotr (ETHICS IN PROGRESS, 2020)
This paper presents a critical evaluation of ethical and philosophical concerns about the effective altruism as an ethical position. Effective altruists claim that one of our important ethical obligations is to do the most good possible, with the biggest possible positive impact. This impact should be measured with rational tools and by evaluating the effectiveness of our actions. At first glance, this might seem as a consensus building position, a good starting point for building a community of people wanting to change the world for the better. In our paper, we present some difficulties which are connected with such a way of thinking about charity and an ethical obligation to donate. We discuss the problem of the commercialization of ethical values, understanding effectiveness, agreeing about goals, as well as the political consequences of effective altruism understood as an ethical position.